Synthesis and biological evaluation of genistein‐O‐alkylamine derivatives as potential multifunctional anti‐Alzheimer agents. (21st October 2018) - Hong, Chen; Guo, Hui‐yan; Chen, Shuai; Lv, Jian‐wu; Zhang, Xin; Yang, Ya‐cheng; Huang, Kang; Zhang, Yi‐juan; Tian, Zhi‐yong; Luo, Wen; Chen, Yi‐ping
Abstract: A series of genistein derivatives were synthesized and evaluated as multifunctional anti‐Alzheimer agents. The results showed that these derivatives had significant acetylcholinesterase (AChE) inhibitory activity; compound5a exhibited the strongest inhibition to AChE with an IC50 value (0.034 μM) much lower than that of rivastigmine (6.53 μM). A Lineweaver–Burk plot and molecular modeling study showed that compound5a targeted both the catalytic active site and the peripheral anionic site of AChE. These compounds also showed potent peroxy scavenging activity and metal‐chelating ability. The compounds did not show obvious effect on HepG2 and PC12 cell viability at the concentration of 100 μM. Therefore, these genistein derivatives can be utilized as multifunctional agents for the treatment of AD. Abstract : A series of genistein‐ O ‐alkylamine derivatives were designed, synthesized, and evaluated as multifunctional anti‐Alzheimer agents. Among them, compound5a was observed to be most potent inhibitor of acetylcholinesterase and butyrylcholinesterase, with IC50 values of 0.034 and 0.33 µM, respectively. These compounds also showed potent peroxyl radical absorbance activity and metal chelating ability. Moreover, they did not affect PC12 and HepG2 cell viability at the concentration of 100 μM.